(5.4*10^-1)(7*10^0) simplify. write each answer in scientific notation

Answers

Answer 1
Answer: (5.4*10^-1)(7*10^0) \n \n  5.4 * 10^(-1) * 7 * 10^0 \ / \ simplify \ brackets \n \n 37.8 * 10^(-1) * 10^0 \ / \ simplify \n \n 37.8 * 10^(-1) \ / \ product \ rule \n \n Answer: 37.8 * 10^(-1)

Related Questions

Solve:3(x - 2) = 18
3/7 + 2/7 as its simpliest form.
How do you solve this 3 = 4x+31/5
Five times a number is the same as 30 more than 8 times the number. Find the number.If n is "the number," which equation could be used to solve for the number? 3n = 30 5n + 8n = 30 5n = 8n + 30
An SUV costs $27,070 and costs an average of $0.18 per mile to maintain. A hybrid model of the SUV costs $32,880 and costs an average of $0.13 per mile to maintain. After how many miles will the cost of the gas-only SUV exceed the cost of hybrid?

What is the value of a if (2a +3) - (4a-8)= 7

Answers

( 2a + 3 ) - ( 4a - 8 ) = 7
2a + 3 - 4a + 8 = 7
-2a + 11 = 7 
-2a = -4
a = -4 / -2
a = 2

3c - 9d + 5d
simplify this

Answers